(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Customary prescription includes the utilization of both material and non-material parts. The material segments constantly include parts or organs of plants and their items. They likewise comprise of creature organs, minerals and other regular substances. The non-material parts, which constitute essential things of religious and otherworldly drugs, incorporate torment, charms, enchantment, mantras, religious verses, talismans and customs like penances, submission of malevolence spirits, and so forth.